Analysis of the fitness effect of compensatory mutations - Zhang, Liqing (HFSP Publishing, 2009)
This paper extends previous work on the Darwinian evolutionary fitness effect of the fixation of deleterious mutations by incorporating compensatory mutations, which are mutations (deleterious by themselves) that ameliorate other deleterious mutations, thus reducing the genetic load of populations. Since having compensatory mutations essentially changes the distributional shapes of deleterious mutations, the effect of compensatory mutations is studied by comparing distributions of deleterious mutations without compensatory mutations to those with compensatory mutations. The effect of effective population size (N(e)), fitness distributional shape, and mutation rate on population fitness reduction is studied. Results indicate that, first, the smaller a population’s N(e), the larger the effect of compensatory mutations on fitness recovery, and the compensatory effect increases sharply with decreasing N(e). Second, the larger the squared coefficient of variation in the fitness effect of deleterious mutations, the larger the effect of compensatory mutations. Third, for fixed N(e), the higher the rate of deleterious mutations, the more effective compensatory mutation is in fitness recovery, and this effect is more pronounced for smaller N(e).